Cold collision and the determination of the X2Σ1/2(v = 1, N = 1) → A2Π1/2(v′ = 0, J′ = 1/2) frequency with buffer-gas-cooled MgF molecules. (October 2019) - Xu, Supeng; Xia, Meng; Gu, Ruoxi; Pei, Chunying; Yang, Zhenghai; Xia, Yong; Yin, Jianping
Highlights: We compare two buffer-gas cell geometries for production of MgF molecules. The collision cross-section of MgF with helium is measured. The accurate frequency of X 2 Σ1/2 ( v = 1, N = 1) → A 2 Π1/2 ( v ′ = 0, J′ = 1/2) transition is measured, as well as some relevant P and Q branches in the low-lying rotational states. Abstract: We report a detailed experimental study of the cold collision of magnesium mono-fluoride (MgF) with buffer gas and compare the cryogenic molecular beam source of two different inner structures of cell. The collision cross section with helium is measured to be ∼ 0.8 × 10 − 14 c m 2 at 7.5 K, which is suitable for buffer-gas cooling. The absorption spectrum around 368.7 nm at low-lying rotational states is assigned and the accurate frequency of X 2 Σ1/2 ( v = 1, N = 1) → A 2 Π1/2 ( v ′ = 0, J′ = 1/2) transition is determined to be 812.959246 THz, which is essential for constructing the quasi-closed cycling between vibrational states. Our study is an important complement to laser cooling of MgF molecules.